"n Kritiese evaluasie van Colin Brown se studie: Miracles and the critical mind - Vledder, E. J. (Hervormde teologiese studies, 1986)
A critical evaluation of Colin Brown's study: Miracles and the critical mind As a historical survey of the viewpoints regarding miracles throughout the ages. Miracles and the critical mind of Colin Brown can be highly recommended as a reference work. In this lies its value. Brown has an interesting viewpoint. He states that miracles can only be interpreted when asked what the evangelists themselves meant by it in their Gospels. But to my mind. Brown does not successfully show that miracles enable us to make sense of the Gospels as history. The reason is that he cannot conclusively prove that miracles are historical facts, and thus the Gospels are history as well. Miracles should be accepted by faith. In this respect he stands fully in an age-old tradition, and as such does not contribute much new towards the debate about miracles. To follow is a critical evaluation of the abovementioned study.